1989
DOI: 10.1021/bi00441a014
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded DNA cleavage/religation reaction of eukaryotic topoisomerase II: evidence for a nicked DNA intermediate

Abstract: The DNA cleavage reaction of eukaryotic topoisomerase II produces nicked DNA along with linear nucleic acid products. Therefore, relationships between the enzyme's DNA nicking and double-stranded cleavage reactions were determined. This was accomplished by altering the pH at which assays were performed. At pH 5.0 Drosophila melanogaster topoisomerase II generated predominantly (greater than 90%) single-stranded breaks in duplex DNA. With increasing pH, less single-stranded and more double-stranded cleavage was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
118
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 63 publications
8
118
0
1
Order By: Relevance
“…Above pH 7.5 or below pH 4.0, little DNA cleavage was detectable. The strongest cleavage was observed at pH 5.0, consistent with the results obtained with both calf thymus and Drosophila TOP2s (19,20). Similar results were obtained with human TOP2␤ (data not shown).…”
Section: Acidic Ph Induces Reversible Top2-mediated Dna Strand Breaks Insupporting
confidence: 90%
See 2 more Smart Citations
“…Above pH 7.5 or below pH 4.0, little DNA cleavage was detectable. The strongest cleavage was observed at pH 5.0, consistent with the results obtained with both calf thymus and Drosophila TOP2s (19,20). Similar results were obtained with human TOP2␤ (data not shown).…”
Section: Acidic Ph Induces Reversible Top2-mediated Dna Strand Breaks Insupporting
confidence: 90%
“…Previous studies have demonstrated that both calf thymus and Drosophila TOP2s induce DNA cleavage at pH below 7.0, with an optimum about 5 (19,20). In the current study, we show that TOP2 is involved in acidic pH-induced DNA damage, mutagenesis, and cytotoxicity.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the enzyme generates cleaved DNA molecules that contain 4-base single-stranded ends at their 5′-termini. [71,72] During its cleavage event, topoisomerase II covalently attaches to these newly generated 5′-termini [48,[71][72][73]. This covalent enzyme-cleaved DNA complex is known as the "cleavage complex.…”
Section: Topoisomerase II Catalytic Cyclementioning
confidence: 99%
“…To maintain genomic integrity during this cleavage event, the enzyme forms covalent bonds between active site tyrosyl residues and the 5′-DNA termini created by scission of the double helix (54)(55)(56). These covalent topoisomerase IIcleaved DNA intermediates are known as cleaVage complexes.…”
mentioning
confidence: 99%